The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1590/s0104-11692007000500017
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of underreported surgical site infection evidenced by post-discharge surveillance

Abstract: The Surgical Site Infection (SSI)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 10 publications
0
5
0
3
Order By: Relevance
“…Different studies have shown that 12%–84% of SSIs are diagnosed after hospital discharge, thereby confirming the importance of post-discharge surveillance in the detection and reporting of SSI rates. 14 …”
Section: Discussionmentioning
confidence: 99%
“…Different studies have shown that 12%–84% of SSIs are diagnosed after hospital discharge, thereby confirming the importance of post-discharge surveillance in the detection and reporting of SSI rates. 14 …”
Section: Discussionmentioning
confidence: 99%
“…In these cases, these institutions tend not to report what actually happens in terms of complications, or limit the findings to the immediate postoperative period. When monitoring is performed only during hospital stay, it does not provide reliable indicators and may lead to underreporting (26,(31)(32) .…”
Section: Discussionmentioning
confidence: 99%
“…Un estudio que analizó métodos de vigilancia post-operatoria en dos hospitales de Sao Paulo (Brasil) encontró 80% de las ISQ diagnosticadas hasta el 14º día después del procedimiento 27 . En un hospital universitario italiano con tasa global de ISQ de 10,6%, el diagnóstico de estas infecciones ocurrió 11,5 días después del procedimiento 23 .…”
Section: Infecciones Asociadas a Atención De Saludunclassified